A quick-drying green low-carbon waterproof mortar for repairing gaps in outdoor doors and windows and a preparation method thereof
By modifying sulfur aluminate cement and silicon powder and using borosilane-containing hydrophobic agent, the combustion performance level, compressive strength and thermal insulation performance of the waterproof mortar are improved, and the safety hazards of waterproof mortar in the prior art and poor insulation and energy-saving effects in the extreme environment are solved.
Patent Information
- Application Number
- CN202411838805.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing waterproof mortar has low combustion performance grade and low compressive strength in extreme environments, which cannot achieve good load-bearing and deformation, and has too high thermal conductivity, resulting in poor thermal insulation and energy-saving effects.
By modifying the sulfur aluminate cement and silicon powder, and using a borosilane-containing hydrophobic agent, the combustion performance level of the waterproof mortar is improved by the synergistic effect between the components, the compressive strength is increased, while maintaining a low thermal conductivity.
The combustion performance level of waterproof mortar is improved, compressive strength is increased, and the thermal conductivity is maintained at a low level, solving the problems of safety hazards, load-bearing capacity and poor thermal insulation and energy-saving effects of waterproof mortar in the latest technology in extreme environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of building materials, and specifically relates to a quick-drying green and low-carbon waterproof mortar for repairing gaps in outdoor doors and windows and a preparation method thereof. Background Art
[0002] Waterproof mortar is a mortar material specially used for waterproofing projects. It achieves waterproof and anti-seepage effects by increasing the density of the mortar and improving its crack resistance. Waterproof mortar not only has good weather resistance and durability, but also has excellent anti-seepage, density and extremely high adhesion, as well as strong waterproof and anti-corrosion effects. Due to its excellent performance, waterproof mortar is widely used in waterproofing and anti-seepage of building exterior walls, basements, pools and water towers, bathrooms, tunnels and bridges.
[0003] A Chinese patent (publication number CN111423193B) discloses a low-absorption, fast-hardening polymer cement waterproof mortar and its preparation method. The waterproof mortar improved by the patent has excellent early and continuous impermeability, low water absorption, high bonding strength, rapid early strength development, no shrinkage in later strength, and can withstand 80°C high temperature treatment for 48 hours and still withstand immersion in water for 48 hours without loss of compressive and flexural strength. It has strong adaptability to the environment and adjustable setting time. However, the patent does not solve the shortcomings and deficiencies of the waterproof mortar in the prior art: (1) low combustion performance level, prone to safety hazards in extreme environments; (2) low compressive strength, unable to achieve good load-bearing and deformation; (3) too high thermal conductivity, resulting in poor insulation and energy-saving effects.
[0004] Therefore, it has become an urgent problem to be solved in the industry to provide a quick-drying, green, low-carbon, waterproof mortar for repairing gaps in outdoor doors and windows, which can effectively improve its combustion performance level and increase its compressive strength by introducing modified components while maintaining a low thermal conductivity. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a quick-drying, green, low-carbon, waterproof mortar for repairing gaps in outdoor doors and windows and a preparation method thereof. By modifying sulphoaluminate cement and silica powder and using a borosilane-containing water-repellent agent, the synergistic effect between the components is utilized to effectively improve the combustion performance level of the waterproof mortar, increase the compressive strength, and maintain a low thermal conductivity.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present application provides a method for preparing a quick-drying green low-carbon outdoor door and window gap repair waterproof mortar, comprising the following steps:
[0008] Step S1: adding 8 to 16 parts of latex powder, 3 to 5 parts of cellulose ether, 15 to 35 parts of silane water repellent, 1 to 2 parts of defoaming agent, 1 to 3 parts of lithium carbonate, 0.5 to 2 parts of PP fiber and 0.5 to 1 part of water reducing agent to 500 to 600 parts of deionized water, stirring at a stirring speed of 20 to 40 rpm for 5 to 10 minutes to obtain a mixed solution A;
[0009] Step S2: In parts by weight, 450-550 parts of sand are added to 500-600 parts of the mixed solution A, and stirred at a stirring speed of 60-80 rpm for 10-20 min; then 280-350 parts of silicate cement, 80-150 parts of modified sulphoaluminate cement composite materials, 30-50 parts of amino silicon powder, 10-20 parts of hollow glass microspheres and 40-60 parts of expanded perlite are added, and stirred at a stirring speed of 100-140 rpm for 6-8 min to obtain a quick-drying green low-carbon outdoor door and window gap repair waterproof mortar.
[0010] In some embodiments of the present application, the preparation method of the modified sulphoaluminate cement composite material includes: adding 2 to 4 parts of polyvinyl pyrrolidone to 100 to 120 parts of deionized water, stirring evenly, and then adding 8 to 10 parts of carboxylated graphene and ultrasonically dispersing for 45 to 60 minutes to obtain a graphene suspension; mixing 100 to 120 parts of the graphene suspension and 130 to 150 parts of sulphoaluminate cement for 5 to 10 minutes, drying, and crushing to obtain a modified sulphoaluminate cement composite material.
[0011] In some embodiments of the present application, the preparation method of the carboxylated graphene includes: adding 1 to 3 parts of graphene oxide to 800 to 1000 parts of deionized water by weight, ultrasonically dispersing for 40 to 60 minutes, then adding 8 to 10 parts of sodium hydroxide and 15 to 20 parts of azobisisobutyronitrile and ultrasonically dispersing for 30 to 40 minutes, reacting at 30 to 35° C. for 4 to 6 hours, washing, and drying to obtain carboxylated graphene.
[0012] In some embodiments of the present application, the particle size of the sulphoaluminate cement is 10-300 μm.
[0013] The graphene oxide in the modified sulphoaluminate cement composite material has a large specific surface area and lamellar structure, and can be evenly dispersed in the mortar to form nanoscale pores. These pores can effectively block the heat transfer path, reduce the thermal conductivity of the material, and improve the thermal insulation performance of the mortar.
[0014] In some embodiments of the present application, the preparation method of the amino silicon powder includes: adding 10 to 15 parts of silicon powder to 100 to 120 parts of deionized water by weight, ultrasonically dispersing at room temperature for 30 to 60 minutes, then adding 1 to 3 parts of 3-aminopropyltriethoxysilane, adjusting the pH to 7.5 to 7.8, stirring the reaction at 70 to 75°C for 10 to 12 hours, centrifuging after the reaction is completed, washing the solid obtained by centrifugation three times with deionized water, and vacuum drying to obtain the amino silicon powder.
[0015] In some embodiments of the present application, the particle size of the silicon powder is 50~500nm.
[0016] Amino silicon powder can be strongly adsorbed on the surface of silicate cement through electrostatic action and hydrogen bonding, and fill the nanopores and micro cracks of the waterproof mortar, making the mortar more compact, reducing the moisture in the gaps between the mortar, and thus improving the compressive strength of the waterproof mortar.
[0017] In some embodiments of the present application, the silane water repellent is a boron-containing silane water repellent; the preparation method of the boron-containing silane water repellent comprises: in parts by weight, 30 to 35 parts of calcium carbonate, 15 to 20 parts of stearic acid, 10 to 12 parts of ethyl orthosilicate and 40 to 46 parts of isopropanol are mixed evenly, and then 10 to 14 parts of sorbitan trioleate are added for emulsification for 30 to 60 minutes, and after the emulsification is completed, 25 to 28 parts of boric acid, 12 to 16 parts of dodecyl triethoxysilane and 30 to 33 parts of dimethyl polysiloxane are added, and stirred at room temperature for 1 to 3 hours to obtain a boron-containing silane water repellent.
[0018] The borosilane-containing water repellent can form a glass-like protective layer covering the surface of the material under the high temperature environment of combustion. This protective layer can effectively isolate oxygen and heat, prevent the flame from spreading further, and thus improve the combustion performance level.
[0019] In some embodiments of the present application, the particle size of the hollow glass microspheres is 10-200 μm.
[0020] In some embodiments of the present application, the particle size of the expanded perlite is 0.1-1 mm.
[0021] The second aspect of the present application provides a quick-drying green and low-carbon waterproof mortar for repairing gaps in outdoor doors and windows prepared by the method described in the first aspect.
[0022] Compared with the prior art, the present application at least achieves the following technical effects: (1) The boron element of the boron-containing silane water repellent of the present invention can promote the formation of a carbon layer of graphene oxide in the modified sulphoaluminate cement composite material during combustion. The carbon layer can block the transfer of heat and oxygen, reduce the volatilization of combustibles, thereby inhibiting combustion and improving the combustion performance level. (2) The boron element of the boron-containing silane water repellent of the present invention works together with the nitrogen element and silicon element in the amino silicon powder. The boron element can form a glassy expansion coating covering the surface of the material to prevent the diffusion of combustible gas; the flame-retardant gas generated by the nitrogen element can be used as a foaming agent to promote the formation of an expanded porous carbon layer, restricting the combustible gas from entering the gas phase to achieve the effect of heat insulation. The silicon element has a low surface energy and is easy to migrate to the surface of the material to form a silicon-containing protective layer, thereby improving the combustion performance level through the synergy of boron-nitrogen-silicon. (3) The modified sulphoaluminate cement composite material of the present invention provides a carboxyl group, which can combine with the amino silicon powder through the amino group to form an interconnected network structure, which can bridge microcracks and prevent the expansion of cracks, thereby improving the compressive strength of the waterproof mortar. (4) The hollow glass microspheres with a particle size of 10-200 μm in the present invention have a high compressive strength, which enables the internal microspheres to provide additional support when the mortar is subjected to external loads, thereby improving the overall compressive strength of the mortar. (5) The present invention uses expanded perlite with a particle size of 0.1-1 mm, which contains a large amount of air in its porous structure. This air is a poor thermal conductor and can effectively block the transfer of heat. Combined with the low thermal conductivity of the expanded perlite itself, the mortar has better thermal insulation performance and effectively reduces heat transfer. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below. However, it should be understood that the description herein is only used to explain the present invention and is not used to limit the scope of the present invention.
[0024] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention, and the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The reagents and instruments used herein are all commercially available, and the characterization means involved can refer to the relevant descriptions in the prior art, which will not be repeated herein.
[0025] The sources of some components in the embodiments and comparative examples are as follows:
[0026] Portland cement, model P·C32.5R, was purchased from Guangdong Qingxin Cement Co., Ltd.;
[0027] Sulphoaluminate cement I, with an average particle size of 20 μm, was purchased from Sanxiang Special Cement Company;
[0028] Sulphoaluminate cement II, with an average particle size of 4 mm, was purchased from Hubei Yicheng Anda Special Cement Co., Ltd.;
[0029] Sand, item number 5768, was purchased from Lingshou County Zehong Mineral Products Processing Plant;
[0030] Silica powder I, product number S130843, average particle size 60 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0031] Silicon powder II, product number PT-Si-1μm, average particle size 1μm, purchased from Shanghai Pantian Powder Materials Co., Ltd.;
[0032] Latex powder, item number 66635, purchased from Shandong Xiongrui Trading Co., Ltd.;
[0033] Cellulose ether, model HPK400M, purchased from Shandong Heda Group Co., Ltd.;
[0034] Hollow glass microspheres I, with an average particle size of 68 μm, were purchased from Shanxi Hainuo Technology Co., Ltd.;
[0035] Hollow glass microspheres II, with an average particle size of 1 mm, were purchased from Langfang Sennuo Glass Microspheres Co., Ltd.;
[0036] Expanded perlite I, with a particle size of 0.425 mm, was purchased from Fanxian Puyu Building Insulation Materials Co., Ltd.;
[0037] Expanded perlite II, particle size 3 mm, purchased from Xinyang Jinhualan Mining Co., Ltd.;
[0038] Commercially available silane water repellent, brand Silres BS 1802, purchased from Shanghai Shangnan New Materials Co., Ltd.;
[0039] Polyether defoamer, product number DF-8201, purchased from Dongguan Defeng Defoamer Co., Ltd.;
[0040] Lithium carbonate, product number PA56804, was purchased from Shanghai Chuangsai Technology Co., Ltd.;
[0041] PP fiber, model 3MM, purchased from Shandong Luke Composite Materials Co., Ltd.;
[0042] Polycarboxylate water reducer, product number QU801, purchased from Shandong World Oilfield Technology Co., Ltd.;
[0043] Graphene oxide, model DN-20DY, was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.;
[0044] Sodium hydroxide, CAS No. 8012-01-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0045] Azobisisobutyronitrile, CAS No. 78-67-1, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0046] Polyvinyl pyrrolidone, product number S30267, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0047] 3-Aminopropyltriethoxysilane, CAS No. 919-30-2; purchased from Shanghai MacLean Company;
[0048] Calcium carbonate, CAS No. 471-34-1, was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0049] Stearic acid, CAS No. 57-11-4, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0050] Tetraethyl orthosilicate, CAS No. 78-10-4, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0051] Isopropyl alcohol, CAS No. 67-63-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0052] Sorbitan trioleate, CAS No. 26658-19-5, was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0053] Boric acid, CAS No. 11113-50-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0054] Dodecyltriethoxysilane, product number D834042, purchased from Guangzhou Xiaofan Technology Co., Ltd.;
[0055] Dimethicone, product number A14727, was purchased from West Asia Chemical Technology (Shandong) Co., Ltd.
[0056] Example 1
[0057] This embodiment provides a method for preparing a quick-drying green low-carbon waterproof mortar for repairing gaps in outdoor doors and windows, comprising the following steps:
[0058] Preparation of modified sulphoaluminate cement composite material: (1) The preparation method of carboxylated graphene includes: adding 3 parts of graphene oxide to 1000 parts of deionized water by weight, ultrasonically dispersing for 60 minutes, then adding 10 parts of sodium hydroxide and 20 parts of azobisisobutyronitrile and ultrasonically dispersing for 40 minutes, reacting at 35°C for 4 hours, washing, and drying to obtain carboxylated graphene. (2) Adding 4 parts of polyvinyl pyrrolidone to 120 parts of deionized water by weight and stirring evenly, then adding 10 parts of carboxylated graphene and ultrasonically dispersing for 60 minutes to obtain a graphene suspension; mixing 120 parts of the graphene suspension and 150 parts of sulphoaluminate cement I (particle size 20 μm, purchased from Sanxiang Special Cement Company) for 10 minutes, drying, and crushing to obtain a modified sulphoaluminate cement composite material.
[0059] Preparation of amino silicon powder: In parts by weight, 15 parts of silicon powder I (particle size 60 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were added to 120 parts of deionized water, ultrasonically dispersed at room temperature for 60 minutes, and then 3 parts of 3-aminopropyltriethoxysilane were added, the pH was adjusted to 7.8, and the reaction was stirred at 75°C for 10 hours. After the reaction was completed, centrifugation was performed, and the solid obtained by centrifugation was washed three times with deionized water and vacuum dried to obtain amino silicon powder.
[0060] Preparation of borosilane water repellent: In parts by weight, 35 parts of calcium carbonate, 20 parts of stearic acid, 12 parts of ethyl orthosilicate and 46 parts of isopropanol are mixed evenly, and then 14 parts of sorbitan trioleate are added and emulsified for 60 minutes. After emulsification, 28 parts of boric acid, 16 parts of dodecyltriethoxysilane and 33 parts of dimethylpolysiloxane are added, and stirred at room temperature for 3 hours to obtain a borosilane water repellent.
[0061] Step S1: adding 16 parts of latex powder, 5 parts of cellulose ether, 35 parts of borosilane water repellent, 2 parts of polyether defoamer, 3 parts of lithium carbonate, 2 parts of PP fiber and 1 part of polycarboxylate water reducer to 600 parts of deionized water, stirring at a stirring speed of 40 rpm for 5 minutes to obtain a mixed solution A;
[0062] Step S2: In parts by weight, 550 parts of sand are added to 600 parts of the mixed solution A, and stirred at a stirring speed of 80 rpm for 10 minutes; then 350 parts of silicate cement, 150 parts of modified sulphoaluminate cement composite materials, 50 parts of amino silicon powder, 20 parts of hollow glass microspheres I (particle size of 68 μm, purchased from Shanxi Hainuo Technology Co., Ltd.) and 60 parts of expanded perlite I (particle size of 0.425 mm, purchased from Fanxian Pu Yu Building Insulation Materials Co., Ltd.) are added, and stirred at a stirring speed of 140 rpm for 6 minutes to obtain a quick-drying green and low-carbon outdoor door and window gap repair waterproof mortar.
[0063] Example 2
[0064] This embodiment provides a method for preparing a quick-drying green low-carbon outdoor door and window gap repair waterproof mortar, comprising the following steps:
[0065] Preparation of modified sulphoaluminate cement composite material: (1) The preparation method of carboxylated graphene includes: adding 1 part of graphene oxide to 800 parts of deionized water by weight, ultrasonically dispersing for 40 minutes, then adding 8 parts of sodium hydroxide and 15 parts of azobisisobutyronitrile and ultrasonically dispersing for 30 minutes, reacting at 30°C for 6 hours, washing, and drying to obtain carboxylated graphene. (2) Adding 2 parts of polyvinyl pyrrolidone to 100 parts of deionized water by weight and stirring evenly, then adding 8 parts of carboxylated graphene and ultrasonically dispersing for 45 minutes to obtain a graphene suspension; mixing 100 parts of the graphene suspension and 130 parts of sulphoaluminate cement I (particle size 20 μm, purchased from Sanxiang Special Cement Company) for 5 minutes, drying, and crushing to obtain a modified sulphoaluminate cement composite material.
[0066] Preparation of amino silicon powder: In parts by weight, 10 parts of silicon powder I (particle size 60 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were added to 100 parts of deionized water, and ultrasonically dispersed at room temperature for 30 minutes. Then, 1 part of 3-aminopropyltriethoxysilane was added, and the pH was adjusted to 7.5. The reaction was stirred at 70°C for 12 hours. After the reaction was completed, centrifugation was performed, and the solid obtained by centrifugation was washed three times with deionized water and vacuum dried to obtain amino silicon powder.
[0067] Preparation of borosilane water repellent: In parts by weight, 30 parts of calcium carbonate, 15 parts of stearic acid, 10 parts of ethyl orthosilicate and 40 parts of isopropanol are mixed evenly, and then 10 parts of sorbitan trioleate are added and emulsified for 30 minutes. After emulsification, 25 parts of boric acid, 12 parts of dodecyltriethoxysilane and 30 parts of dimethylpolysiloxane are added, and stirred at room temperature for 1 hour to obtain a borosilane water repellent.
[0068] Step S1: adding 8 parts of latex powder, 3 parts of cellulose ether, 15 parts of borosilane water repellent, 1 part of polyether defoamer, 1 part of lithium carbonate, 0.5 parts of PP fiber and 0.5 parts of polycarboxylate water reducer to 500 parts of deionized water, stirring at a stirring speed of 20 rpm for 10 minutes to obtain a mixed solution A;
[0069] Step S2: In parts by weight, 450 parts of sand are added to 500 parts of the mixed solution A, and stirred at a stirring speed of 60 rpm for 20 minutes; then 280 parts of silicate cement, 80 parts of modified sulphoaluminate cement composite materials, 30 parts of amino silicon powder, 10 parts of hollow glass microspheres I (particle size of 68 μm, purchased from Shanxi Hainuo Technology Co., Ltd.) and 40 parts of expanded perlite I (particle size of 0.425 mm, purchased from Fanxian Pu Yu Building Insulation Materials Co., Ltd.) are added, and stirred at a stirring speed of 100 rpm for 8 minutes to obtain a quick-drying green and low-carbon outdoor door and window gap repair waterproof mortar.
[0070] Example 3
[0071] This embodiment provides a method for preparing a quick-drying green low-carbon outdoor door and window gap repair waterproof mortar, comprising the following steps:
[0072] Preparation of modified sulphoaluminate cement composite material: (1) The preparation method of carboxylated graphene includes: adding 2 parts of graphene oxide to 900 parts of deionized water by weight, ultrasonically dispersing for 50 minutes, then adding 9 parts of sodium hydroxide and 18 parts of azobisisobutyronitrile and ultrasonically dispersing for 35 minutes, reacting at 32°C for 5 hours, washing, and drying to obtain carboxylated graphene. (2) Adding 3 parts of polyvinyl pyrrolidone to 110 parts of deionized water by weight and stirring evenly, then adding 9 parts of carboxylated graphene and ultrasonically dispersing for 50 minutes to obtain a graphene suspension; mixing 110 parts of the graphene suspension and 140 parts of sulphoaluminate cement I (particle size 20 μm, purchased from Sanxiang Special Cement Company) for 8 minutes, drying, and crushing to obtain a modified sulphoaluminate cement composite material.
[0073] Preparation of amino silicon powder: In parts by weight, 12 parts of silicon powder I (particle size 60 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were added to 110 parts of deionized water, ultrasonically dispersed at room temperature for 40 minutes, and then 2 parts of 3-aminopropyltriethoxysilane were added, the pH was adjusted to 7.6, and the reaction was stirred at 72°C for 11 hours. After the reaction was completed, centrifugation was performed, and the solid obtained by centrifugation was washed three times with deionized water and vacuum dried to obtain amino silicon powder.
[0074] Preparation of borosilane water repellent: In parts by weight, 32 parts of calcium carbonate, 18 parts of stearic acid, 11 parts of ethyl orthosilicate and 42 parts of isopropanol are mixed evenly, and then 12 parts of sorbitan trioleate are added and emulsified for 50 minutes. After emulsification, 26 parts of boric acid, 14 parts of dodecyltriethoxysilane and 32 parts of dimethylpolysiloxane are added, and stirred at room temperature for 2 hours to obtain a borosilane water repellent.
[0075] Step S1: adding 10 parts of latex powder, 4 parts of cellulose ether, 25 parts of borosilane water repellent, 2 parts of polyether defoamer, 2 parts of lithium carbonate, 1 part of PP fiber and 0.8 parts of polycarboxylate water reducer to 550 parts of deionized water, stirring at a stirring speed of 30 rpm for 8 minutes to obtain a mixed solution A;
[0076] Step S2: In parts by weight, 500 parts of sand are added to 550 parts of the mixed solution A, and stirred at a stirring speed of 70 rpm for 15 minutes; then 300 parts of silicate cement, 100 parts of modified sulphoaluminate cement composite material, 40 parts of amino silicon powder, 15 parts of hollow glass microspheres I (average particle size of 68 μm, purchased from Shanxi Hainuo Technology Co., Ltd.) and 50 parts of expanded perlite I (particle size of 0.425 mm, purchased from Fanxian Pu Yu Building Insulation Materials Co., Ltd.) are added, and stirred at a stirring speed of 120 rpm for 7 minutes to obtain a quick-drying green and low-carbon outdoor door and window gap repair waterproof mortar.
[0077] Comparative Example 1
[0078] This comparative example provides a method for preparing a waterproof mortar, which differs from Example 1 in that commercially available sulphoaluminate cement I is used instead of the modified sulphoaluminate cement composite material, commercially available silica powder I is used instead of amino silica powder, and commercially available silane water repellent is used instead of the boron-containing silane water repellent.
[0079] Comparative Example 2
[0080] This comparative example provides a method for preparing a waterproof mortar, which differs from comparative example 1 in that a boron-containing silane water repellent is used instead of a commercially available silane water repellent.
[0081] Comparative Example 3
[0082] This comparative example provides a method for preparing a waterproof mortar, which differs from comparative example 1 in that a modified sulphoaluminate cement composite material is used instead of commercially available sulphoaluminate cement I.
[0083] Comparative Example 4
[0084] This comparative example provides a method for preparing a waterproof mortar, which differs from comparative example 3 in that commercially available sulphoaluminate cement II (particle size of 4 mm, purchased from Hubei Yicheng Anda Special Cement Co., Ltd.) is used instead of commercially available sulphoaluminate cement I (particle size of 20 μm, purchased from Sanxiang Special Cement Co., Ltd.) to prepare a modified sulphoaluminate cement composite material.
[0085] Comparative Example 5
[0086] This comparative example provides a method for preparing a waterproof mortar, which differs from comparative example 1 in that amino silicon powder is used instead of commercially available silicon powder I.
[0087] Comparative Example 6
[0088] This comparative example provides a method for preparing a waterproof mortar. The difference from comparative example 5 is that commercially available silicon powder II (particle size of 1 μm, purchased from Shanghai Pantian Powder Material Co., Ltd.) is used instead of commercially available silicon powder I (particle size of 60 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) to prepare amino silicon powder.
[0089] Comparative Example 7
[0090] This comparative example provides a method for preparing a waterproof mortar, which differs from Example 1 in that commercially available hollow glass microspheres II (with a particle size of 1 mm, purchased from Langfang Senno Glass Microsphere Co., Ltd.) are used instead of commercially available hollow glass microspheres I (with a particle size of 68 μm, purchased from Shanxi Hainuo Technology Co., Ltd.).
[0091] Comparative Example 8
[0092] This comparative example provides a method for preparing a waterproof mortar, which differs from Example 1 in that commercially available expanded perlite II (particle size of 3 mm, purchased from Xinyang Jinhualan Mining Co., Ltd.) is used instead of commercially available expanded perlite I (particle size of 0.425 mm, purchased from Fanxian Pu Yu Building Insulation Materials Co., Ltd.).
[0093] The waterproof mortar prepared in the above examples and comparative examples was subjected to the following tests: the combustion performance grade was tested with reference to the requirements of GB / T20473-2021 Building Thermal Insulation Mortar; the compressive strength was tested with reference to the requirements of JC / T 984-2011 Polymer Cement Waterproof Mortar; the thermal conductivity was tested with reference to the requirements of GB / T 20473-2021 Building Thermal Insulation Mortar. The performance test results are shown in Table 1:
[0094] Table 1 Performance test results
[0095]
[0096] It can be seen from the above performance test results that Examples 1-3 have good effects, with a combustion performance grade of A, a compressive strength of 9.1~9.4MPa, and a thermal conductivity of 0.162~0.168W / (m·K); this is because the present invention modifies the sulphoaluminate cement and silica powder and uses a borosilane hydrophobic agent, and with the help of the synergistic effect between the components, effectively improves the combustion performance grade of the waterproof mortar, increases the compressive strength, and maintains a low thermal conductivity.
[0097] The comparative examples, however, are significantly inferior to the examples in the corresponding performance tests because they do not adopt the necessary technical solutions. Compared with Example 1, in Comparative Example 1, commercially available sulphoaluminate cement I is used to replace the modified sulphoaluminate cement composite material, commercially available silicon powder I is used to replace the amino silicon powder, and commercially available silane water repellent is used to replace the boron-containing silane water repellent, so the combustion performance level is reduced, the compressive strength is reduced, and the thermal conductivity is increased. Compared with Comparative Example 1, Comparative Example 2 uses a boron-containing silane water repellent to replace the commercial silane water repellent, and the combustion performance level is improved. Compared with Comparative Example 1, Comparative Example 3 uses a modified sulphoaluminate cement composite material to replace the commercial sulphoaluminate cement I, and the thermal conductivity is reduced. Compared with Comparative Example 3, Comparative Example 4 uses commercially available sulphoaluminate cement II to replace the commercial sulphoaluminate cement I to prepare a modified sulphoaluminate cement composite material. Since the particle size of the commercially available sulphoaluminate cement II is too large, the modification effect is poor, so the thermal conductivity is reduced. Compared with Comparative Example 1, Comparative Example 5 uses amino silicon powder to replace commercial silicon powder I, and the compressive strength increases. Compared with Comparative Example 5, Comparative Example 6 uses commercial silicon powder II to replace commercial silicon powder I to prepare amino silicon powder. Since the particle size of commercial silicon powder II is too large, the modification effect is not good, so the compressive strength is reduced. Compared with Example 1, Comparative Example 7 uses commercial hollow glass microspheres II to replace commercial hollow glass microspheres I. Since the particle size of commercial hollow glass microspheres II is too large, it cannot be dispersed evenly, so the effect of bearing external loads is poor, so the compressive strength is reduced. Compared with Example 1, Comparative Example 8 uses commercial expanded perlite II to replace commercial expanded perlite I. Since the particle size of commercial expanded perlite II is large, the porous structure is less, and the thermal insulation performance is poor, the thermal conductivity is increased.
[0098] The applicant declares that the present application is explained through the above-mentioned embodiments, but the present application is not limited to the above-mentioned embodiments, that is, it does not mean that the present application must rely on the above-mentioned embodiments to be implemented. The technicians in the relevant technical field should understand that any improvement to the present application, the equivalent replacement of the raw materials of the product of the present application, the addition of auxiliary components, the selection of specific methods, etc., all fall within the scope of protection and disclosure of the present application.
[0099] The preferred embodiments of the present application are described in detail above; however, the present application is not limited to the specific details in the above embodiments. Within the technical concept of the present application, a variety of simple modifications can be made to the technical solution of the present application, and these simple modifications all fall within the protection scope of the present application.
[0100] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this application will not further describe various possible combinations.
Claims
1. A method for preparing a quick-drying green low-carbon outdoor door and window gap repair waterproof mortar, characterized in that: The following steps are involved: Step S1: adding 8 to 16 parts of latex powder, 3 to 5 parts of cellulose ether, 15 to 35 parts of silane water repellent, 1 to 2 parts of defoaming agent, 1 to 3 parts of lithium carbonate, 0.5 to 2 parts of PP fiber and 0.5 to 1 part of water reducing agent to 500 to 600 parts of deionized water, stirring at a stirring speed of 20 to 40 rpm for 5 to 10 minutes to obtain a mixed solution A; Step S2: In parts by weight, 450-550 parts of sand are added to 500-600 parts of the mixed solution A, and stirred at a stirring speed of 60-80 rpm for 10-20 min; then 280-350 parts of silicate cement, 80-150 parts of modified sulphoaluminate cement composite materials, 30-50 parts of amino silicon powder, 10-20 parts of hollow glass microspheres and 40-60 parts of expanded perlite are added, and stirred at a stirring speed of 100-140 rpm for 6-8 min to obtain a quick-drying green low-carbon outdoor door and window gap repair waterproof mortar; The preparation method of the modified sulphoaluminate cement composite material comprises: adding 2 to 4 parts of polyvinyl pyrrolidone to 100 to 120 parts of deionized water by weight and stirring evenly, then adding 8 to 10 parts of carboxylated graphene and ultrasonically dispersing for 45 to 60 minutes to obtain a graphene suspension; mixing 100 to 120 parts of the graphene suspension and 130 to 150 parts of sulphoaluminate cement for 5 to 10 minutes, drying, and crushing to obtain a modified sulphoaluminate cement composite material; The preparation method of the carboxylated graphene comprises: adding 1 to 3 parts of graphene oxide to 800 to 1000 parts of deionized water by weight, ultrasonically dispersing for 40 to 60 minutes, then adding 8 to 10 parts of sodium hydroxide and 15 to 20 parts of azobisisobutyronitrile and ultrasonically dispersing for 30 to 40 minutes, reacting at 30 to 35° C. for 4 to 6 hours, washing, and drying to obtain the carboxylated graphene; The particle size of the sulphoaluminate cement is 10-300 μm; The preparation method of the amino silicon powder comprises: adding 10 to 15 parts of silicon powder to 100 to 120 parts of deionized water by weight, ultrasonically dispersing at room temperature for 30 to 60 minutes, then adding 1 to 3 parts of 3-aminopropyltriethoxysilane, adjusting the pH to 7.5 to 7.8, stirring and reacting at 70 to 75° C. for 10 to 12 hours, centrifuging after the reaction is completed, washing the solid obtained by centrifugation with deionized water three times, and vacuum drying to obtain the amino silicon powder; The silane water repellent is a boron-containing silane water repellent; the preparation method of the boron-containing silane water repellent comprises: in parts by weight, 30-35 parts of calcium carbonate, 15-20 parts of stearic acid, 10-12 parts of ethyl orthosilicate and 40-46 parts of isopropanol are mixed evenly, and then 10-14 parts of sorbitan trioleate are added for emulsification for 30-60 minutes, and after the emulsification is completed, 25-28 parts of boric acid, 12-16 parts of dodecyl triethoxysilane and 30-33 parts of dimethyl polysiloxane are added, and stirred at room temperature for 1-3 hours to obtain the boron-containing silane water repellent.
2. The method for preparing a quick-drying green low-carbon outdoor door and window gap repair waterproof mortar according to claim 1, characterized in that: The particle size of the silicon powder is 50-500 nm.
3. The method for preparing a quick-drying green low-carbon outdoor door and window gap repair waterproof mortar according to claim 1, characterized in that: The particle size of the hollow glass microspheres is 10-200 μm.
4. The method for preparing a quick-drying green low-carbon outdoor door and window gap repair waterproof mortar according to claim 1, characterized in that: The particle size of the expanded perlite is 0.1-1 mm.
5. A quick-drying green low-carbon waterproof mortar for repairing gaps in outdoor doors and windows, characterized in that: Prepared according to the method according to any one of claims 1 to 4.
Citation Information
Patent Citations
A fast-setting polymer cement waterproof mortar with low water absorption and its preparation method
CN111423193B
Waterproof heat-insulating mortar and preparation method thereof
CN108546041A